Pediatric Intensive Care Unit in a Developing Nation: Exploring Acute Neurological Illnesses and Their Clinical Course - Khanal, Babita; Singh, Sandip K; Mishra, Rajnish; Kafle, Prakash; Yadav, Deepk; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2023)
Introduction: The burden of neurological illnesses is high in pediatric age group. Both primary neurological illnesses and neurological complication of systemic illness are commonly seen in pediatric intensive care unit (PICU). Neurological illness prolongs the length of PICU stay and also increases the mortality and morbidity. To assess the burden and describe the spectrum of acute neurological illness in a pediatric intensive care unit and analyze the early outcome.Methods: This is a prospective observational study conducted in Department of Pediatric intensive care unit from April 2021 to March 2022. All children from 1 months to 16 years of age with neurological illness being admitted to PICU were included in the study. Basic demographic characters, diagnosis, treatment modalities and outcome were analyzed.Results: During study period, 237 (24.89%) were admitted to PICU with neurological illness. Mean age was 66 ± 42 months and 138 (58.22%) were male. Out of 237 children, 196 (82.70%) had primary neurological illness and 41 (17.30%) neurosurgical diagnosis. In primary neurological illness, 102 (52.10%) had primary CNS infection, followed by status epilepticus (21.52%), septic encephalopathy (11.70%), neuromuscular illness (8.16%), and metabolic encephalopathy (4.08%). In neurosurgical cases, 32 (78.04%) had Traumatic Brain Injury and 9 (22%) were shifted to PICU postoperatively. Mechanical ventilation was required in 156 (65.82%) and 88 (37.13%) required inotropic support. The mortality rate in neurological cases was 24 (10.12%) as compared to overall mortality rate of 6.8% in PICU.Conclusion: Neurological disorders are common in PICU and are associated with higher mortality rate. Primary CNS infection, severe traumatic brain injury and status epilepticus were common cause of PICU admission in our cohort.